An?lise de m?todos de position size em um sistema de negocia??o em bolsa de valores para a minimiza??o do risco - Queiroz, Indiara da Silva Santana (2018)
Profitable trading systems with high hit rates can become losers when position sizing (PS) is not done correctly. In this research, a profitable trend following trading system was used in which 8 position size methods were implemented to be applied to the brazilian stock exchange futures market, from 01/05/2005 to 01/05/2016. As the performance of the PS methods is closely related to the choice of its parameters, two methodologies were implemented: the optimization method and the Monte Carlo (MC) simulation method. The definition of the most adequate parameter was obtained by limiting the drawdown and maximizing the return. The performance analysis of these PS methods is performed based on the return risk ratio (CAR / MDD) and the results indicated that the PS profit risk presented the best result for the optimization methodology and the PS fixed size for the methodology using the simulation of MC.